How Marketing Ethics Drives Customer Loyalty Through Consumer Empowerment in the Skincare Industry - Catharina Clara; Cindy Devilia Putri (Bina Nusantara University, 2026)
This study aims to examine the effect of marketing ethics on customer loyalty with consumer empowerment as a mediating variable in the skincare industry. Grounded in Self-Determination Theory (SDT), this research adopts a quantitative approach using survey data collected from 206 respondents who have used skincare products. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both measurement and structural models. The results indicate that marketing ethics has a positive and significant effect on customer loyalty and consumer empowerment, while consumer empowerment also significantly influences customer loyalty. Furthermore, consumer empowerment is found to act as a complementary mediator, suggesting that ethical marketing strengthens loyalty both directly and indirectly by enhancing consumers’ sense of autonomy and control. These findings highlight the importance of transparency, honesty, and responsible communication in fostering long-term customer relationships. In conclusion, ethical marketing practices not only strengthen customer-brand relationships but also empower consumers, ultimately leading to sustainable customer loyalty.